Pengaruh Dana Pihak Ketiga Dan Rasio Keuangan Terhadap Bagi Hasil Mudharabah Dengan Return On Asset Sebagai Variabel Moderating Pada Bank Umum Syariah Periode (2017-2021) - Sri Sudiarti; Wahyu Syarvina; Irani Eka Putri Pohan (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The purpose of this study is to find out how much influence DPK, CAR, FDR and ROA have on Mudharabah Profit Sharing at Islamic Commercial Banks for the 2017-2021 period. The data in this study are secondary data obtained from the official website of the Financial Services Authority. This research uses a descriptive approach with a quantitative research type. The results of this study are that the Third Party Funds (DPK) variable has a partial positive and significant effect on Mudharabah Profit Sharing (BHM) at Islamic Commercial Banks for the 2017-2021 period, the Capital Adequacy Ratio (CAR) variable has a partial positive and significant effect on Profit Sharing Mudharabah (BHM) in Islamic Commercial Banks for the 2017-2021 period, the Financing To Deposit Ratio (FDR) variable partially has a positive and significant effect on Mudharabah Profit Sharing (BHM) in Islamic Commercial Banks for the 2017-2021 period, Return On Assets (ROA) can moderate by strengthening the influence of Third Party Funds (DPK) variables on Mudharabah Profit Sharing (BHM) at Islamic Commercial Banks for the 2017-2021 period, Return On Assets (ROA) cannot moderate by weakening the effect of the Capital Adequacy Ratio (CAR) variable on Mudharabah Profit Sharing (BHM) in Islamic Commercial Banks for the 2017-2021 period and Return On Assets (ROA) are able to moderate by strengthening the influence of the Financing To Deposition variable t Ratio (FDR) to Mudharabah Profit Sharing (BHM) at Islamic Commercial Banks for the 2017-2021 period.